PENGEMBANGAN MEDIA PEMBELAJARAN BERBASISWILMO (WEB-BASED INTERACTIVE LEARNING MODULES)UNTUK MENDUKUNG PROSES PEMBELAJARAN TIK SISWA SMA - Lovi Triono, - (2011)
The research, entitled "Learning Media Development Based WILMO (Web Based Interactive Learning Modules) To Support The Learning Process In ICT Senior High School" aims to design and develop media WILMO based learning to support the availability of interactive learning modules that integrated with web-based as the interaction and evaluation of high school students in ICT learning in order to support the learning process. Media prepared by the method developed with the research and development (R&D). The results of this research is a media completely with the models based on the exploratory studies and literature that has been done previously. Before use the media, media has been done verification and validation by an expert in the media in terms of software engineering, IMK, and databases and expert educational innovation in terms of relevance, efficiency, effectiveness and flexibility of the media. The result by used the media showed an increase in learning achievement of students who use the media seen from the experimental classes gain value is greater than the gain control class. Questionnaire results also showed a positive response of students who use the media WILMO.